Occupational, personal and psychosocial resources for preventing persistent low back pain - Melloh, Markus; Salathé, C.; Elfering, A.; Käser, A.; Barz, T.; Aghayev, E.; Röder, C.; Theis, J. (2013)
The aim of this prospective cohort study was to identify modifiable protective factors of the progression of acute/subacute low back pain (LBP) to the persistent state at an early stage to reduce the socioeconomic burden of persistent LBP. Patients attending a health practitioner for acute/subacute LBP were assessed at baseline addressing occupational, personal and psychosocial factors, and followed up over 12 weeks. Pearson correlations were calculated between these baseline factors and the presence of nonpersistent LBP at 12-week follow-up. For those factors found to be significant, multivariate logistic regression analyses were performed. The final 3-predictor model included job satisfaction, mental health and social support. The accuracy of the model was 72%, with 81% of nonpersistent and 60% of persistent LBP patients correctly identified. Further research is necessary to confirm the role of different types of social support regarding their prognostic influence on the development of persistent LBP.